RHEUMATIC HEART DISEASE SCREENING USING HANDHELD ECHOCARDIOGRAPHY: A STUDY AMON`G JUNIOR HIGH SCHOOL STUDENTS IN INDONESIA - Ardini, Tengku Winda; Muttaqien, Chairiza; Sitompul, Opim Salim; Hasan, Refli; Effendy, Elmeid; Rusda, Muhammad (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Considering the high burden of morbidity and mortality associated with Rheumatic Heart Disease (RHD) in Indonesia, there is increasing interest in assessing cost-effective screening modalities, particularly the application of handheld echocardiography. Our study aimed to determine the prevalence of Rheumatic Heart Disease (RHD) in Batu Bara, North Sumatra, Indonesia. Our descriptive observational study was carried out in the Batu Bara region of North Sumatra in May 2025. The study population comprised junior high school students aged 10 to 15 years from a selected school in Batu Bara. Data collection included sociodemographic variables, parental characteristics, environmental and household factors, anthropometric measurements, physical examination findings, auscultation results, and echocardiographic evaluations. All data were analyzed using descriptive statistical methods. A total of 190 children were assessed in this study, with a median age of 13 years, and females comprised 54.7% of the participants. Echocardiographic screening detected Rheumatic Heart Disease (RHD) in three participants, corresponding to a prevalence of 1.6%. Within our study population, the prevalence of RHD was 1.6%. Expansion of echocardiographic screening programs is warranted to comprehensively establish RHD prevalence, accurately evaluate disease burden, and facilitate earlier detection to mitigate adverse clinical outcomes.